The influence of musculoskeletal variables on throwing performance in amateur and elite South African cricketers - Ahmed, Safwaan (Department of Human Biology, 2020)
The game of cricket consists of batting, bowling and fielding. Each of these disciplines require different skills and physical capabilities. The literature exploring these disciplines have traditionally focused on batting and bowling with little research on fielding. However, the increase in popularity of the T20 cricket format has highlighted the importance of optimal fielding performance on the outcome of the game. Efficient fielding requires timely ball retrieval and a well-executed return-throw with the aim of dismissing a batsman or reducing the run rate. The novelty in this research lies in its meaningful contribution in identifying and understanding the musculoskeletal factors that contribute to optimal throwing performance specifically in cricket fielding. These factors may help in the development of an exercise intervention aimed at improving throwing performance in cricketers. The aim of this thesis was to determine and understand the influence of musculoskeletal variables on throwing performance in cricketers. Further it was to compare the musculoskeletal profile between amateur and elite cricketers and to investigate if the factors that contribute to throwing performance were different between the two groups Optimal throwing performance (speed and accuracy) is built on a complex interaction of multiple physical and visuomotor variables. An overview of the literature (Chapter 2) describes the multi-faceted contribution of a range of variables to throwing performance. It includes the contributions and interactions of both the musculoskeletal system and throwing biomechanics to throwing performance. It further compares the musculoskeletal and biomechanical profile of a cricketer to a baseballer and other throwers, as well as compares differences between amateur and elite throwers in relation to throwing performance. While baseballers have been described as superior throwers to cricketers, it is important to understand that the factors that make up optimal performance between the populations are different. Cricketers appear to have a different musculoskeletal profile compared to other throwers such as baseball pitchers. For example, cricketers do not demonstrate an increased shoulder external rotation gain as demonstrated by many throwers and have a markedly reduced shoulder rotational strength and hip strength compared to baseball players, amongst other factors. Biomechanically, cricketers tend to throw with a more side arm position with less shoulder external rotation which has been found to be an inferior position compared to an overhead throwing technique when considering both velocity and accuracy. In addition, playing experience and workload within the same sport may also influence the contributors to performance. Cricketers have been shown to have a lower workload threshold with regard to injury risk, compared to baseball, and therefore mismanagement of throwing workloads specific to cricket may have implications on injury risk and subsequently throwing performance. It can therefore be understood that optimal throwing performance is best achieved when training is not only customised to the sport, but to each individual player as well. The thesis includes two original papers. The first research paper describes the association between musculoskeletal variables and a throwing performance test to evaluate amateur cricketers. Throwing performance included ball velocity and a novel throwing accuracy test. The musculoskeletal variables included strength, range of movement, stability tests which have been previously used to investigate overhead athletes in a number of sports, for both injury prevention and performance. The aim of the second paper was to evaluate elite athletes with the same testing battery to identify if there were differences in musculoskeletal profile and throwing performance between cricketers at different playing levels and whether similar musculoskeletal factors accounted for throwing performance for the two groups. Data collection involved three main steps. First, demographic data, injury history, training experience and a shoulder function questionnaire was completed by participants. Secondly, musculoskeletal testing which included strength measures of the shoulder complex and hip, shoulder range of motion measures, scapula upward rotation positions and an upper-limb endurance test was performed on participants. Lastly, participants completed a throwing performance test which was performed indoors to control for environmental conditions. A maximal throwing speed test (measured with a radar gun) required players to throw over a distance of 20 m, as well as a maximal accuracy test which used a novel target board was performed. To investigate the association between musculoskeletal variables and throwing speed (TS) and accuracy (TA), bivariate analysis and multivariate linear regression analyses was performed for both groups. Paper 1 documents the association between a range of musculoskeletal variables and throwing performance (TP) in amateur cricketers. Of the 31 musculoskeletal variables, only one variable correlated with TS and one variable with TA. Specifically, hip abduction strength was positively associated with TS (r = 0.38) (p = 0.015): on average, a strength increase of 10 Newtons (N) was associated with an increase in TS of 0.60 km/h (95% CI: 0.12-1.08). Nondominant pectoralis minor length correlated positively with TA (r = 0.52) (p = 0.004): on average, a one-centimetre increase in the length correlated to an increase, of 0.633 points (95% CI: 0.225 - 1.041). Paper 2 documents the musculoskeletal variables that were associated with TP in elite cricketers, in addition to musculoskeletal differences between elite and amateur cricketers. Of the 31 musculoskeletal variables only one variable correlated with TS and one with TA in the elite group. Specifically, horizontal adduction range of motion was positively associated with TS (r = 0.38) (p = 0.045), on average, a one-degree increase in shoulder horizontal adduction range of motion was associated with an increase in TS of 0.46 km/h (95% CI: 0.012 - 0.920). Dominant internal rotation strength correlated positively with TA (r = 0.45) (p = 0.019): on average, a strength increase of 10 N was associated with an increase, of 0.34 points (95% CI: 0.06 – 0.62). Throwing speed and TA between groups were not significantly different. Six of the thirty-one musculoskeletal variables measured were found to be significantly different between groups. This signified that firstly, players of different levels may have different musculoskeletal profiles even when playing the same sport. Secondly this highlighted that even while TP had been similar, the variables that were associated with performance were different. The relationship between musculoskeletal variables and TP was further evaluated for the combined group of cricketers. In a combined group statistic, internal rotation strength (r = 0.35) and hip abduction strength (r = 0.72) were both positively correlated with TS (p < 0.05) while pectoralis minor length was positively correlated with TA (r = 0.50) (p < 0.05). In conclusion, from an array of musculoskeletal variables, throwing speed was positively associated with hip abduction strength in the amateur and combined groups, internal rotation strength in the combined group only, and horizontal adduction range of motion in the elite group only. Throwing accuracy was found to be associated with pectoralis minor length in the amateur and combined groups, and internal rotation strength in the elite group only. The musculoskeletal variables linked to TP were different between amateur and elite players. Further, the musculoskeletal profile of cricketers varied between experience levels. This suggests that optimal throwing performance interventions should be based on individual player assessment, or at the very least should be designed to the relevant game and experience level. A future controlled trial should investigate whether an exercise intervention aimed at increasing hip abduction strength in the amateur group, horizontal adduction range in the elite group, and shoulder internal rotation strength in both groups can improve TS; and whether increasing shoulder internal rotation strength in the elite group, and pectoralis minor length in both groups can improve TA.